Relative age effect in formal musical training - Román-Caballero, Rafael; Trujillo, Laura; Martín-Sánchez, Paulina del Carmen; Trainor, Laurel J.; Huertas, Florentino; Martín-Arévalo, Elisa; Lupiáñez, Juan (Cognitive development, 2025)
Access to musical training depends on various factors, such as socioeconomic status and musical background of families, and the child's interest in learning music (related to their openness to experience). In the present study, we show an additional source of selection bias that has gone unnoticed: the relative age of children within the same cohort, when a selection process is implemented. The consequences of this grouping are known as the relative age effect, ranging from academic outcomes to self-esteem. In youth sports, there has been observed an overrepresentation of athletes born in the two first quarters compared to those born later. This study shows a similar unbalance across Spanish music conservatory courses in two samples: a Primary Sample of participants assessed by our research group (N = 322; 33 % of children born in the first quarter vs. 21 % in the fourth quarter, V = .12) and a Secondary Sample comprised by the complete census of six conservatories in Spain (N = 2182; 27 % vs. 24 %, V = .04). This bias was larger when computed on those participants selecting the most popular instrument. In our sample, the relative age of the children and adolescents was independent of other sources of selection bias, such as socioeconomic status. Moreover, the relative age effect was stable across conservatory courses, pointing to an enrolment bias and the impact of a lack of adjustment in the conservatory entrance exam. •Grouping students into annual age bands can have both immediate and long-term effects: relative age effect.•In the case of sports, there is an overrepresentation of children born right before the cohort cutoff.•Access to musical training depends on various factors, such as socioeconomic status.•Here, we show that relative age effect is a source of selection bias that has gone unnoticed.•Overrepresentation of children attending the Spanish music conservatory born in the first trimester of the year.